2020
DOI: 10.34172/jnp.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in COVID-19; a review on current knowledge

Abstract: Coronaviruses are a large family of viruses that can cause a variety of diseases in humans. Some coronaviruses cause only mild illnesses like the common cold. While, some coronaviruses such as SARS-CoV (SARS-associated coronavirus) and Middle East respiratory syndrome coronavirus (MERS-CoV) have, in recent years, been able to cause severe respiratory involvement (pneumonia), leading to death in several patients. By identifying the genomic sequence of the new human coronavirus SARS-CoV-2 (severe acute respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 71 publications
0
22
0
1
Order By: Relevance
“…The underlying mechanisms remain unknown. The design of the current study did not allow us to formally distinguish acute tubular necrosis (ATN) caused by a septic condition before D0 or admission to hospital, or low-oxygen delivery to tissues from specific cytopathic lesions caused by SARS-CoV-2 itself [ 17 ]. Some preliminary results with kidney biopsies (including electronic microscopy) suggest direct virus-mediated tubular injury [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanisms remain unknown. The design of the current study did not allow us to formally distinguish acute tubular necrosis (ATN) caused by a septic condition before D0 or admission to hospital, or low-oxygen delivery to tissues from specific cytopathic lesions caused by SARS-CoV-2 itself [ 17 ]. Some preliminary results with kidney biopsies (including electronic microscopy) suggest direct virus-mediated tubular injury [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al [ 2 ] also found an association between kidney involvement, including proteinuria (by dipstick), and in-hospital death. Once again, the design of our study only allows to generate hypotheses to explain the higher mortality rate in patients with abnormal proteinuria (higher viral load and early multiple organ involvement [ 17 , 29 ] or marker of ATN and/or AKI). Association is not causation, and the main cause of death in COVID-19 was respiratory failure, not kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, amidst the COVID-19 pandemic, which is already taking a toll on global health, early diagnosis and identification of the underlying etiology are essential to guide proper management. Appropriate infectious control, intravenous fluid management, and respiratory failure management can contribute to preventing further AKIs (2,(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…The 2019 novel coronavirus enters human cells by binding its spike to the angiotensin-converting enzyme 2 (ACE2) receptor. Proximal tubular cells and podocytes express the ACE2 receptor, resulting in AKI by virus-induced cytopathic effect, which is manifested by hematuria, proteinuria, elevated levels of blood urea nitrogen (BUN), and serum creatinine [2]. In our case-series, AKI was de ned according to kidney disease improving global outcomes (KDIGO) guideline [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are several mechanisms leading to kidney injury in patients with COVID-19 including cytokine storm syndrome, rhabdomyolysis, hypoxia, and dehydration due to fever or decreased intake of uids. In addition, direct virus invasion to the renal tubular cells may contribute to kidney injury [2].…”
Section: Introductionmentioning
confidence: 99%